Indigenous knowledge of local communities about edible plants in Zebarkhan rangelands in Neyshabur - Morvarid Hosseini; Mohamad Rahim Forouzeh; Hossein Barani (Dānishhā-yi būmī-i Īrān, 2018)
One method used to answer the human concerns in modern society is referring to the empirical knowledge of the past and using the wisdom of the local people's historical knowledge. Among this valuable knowledge, indigenous knowledge is unique in identifying edible plants and their consumption practices in local communities. Therefore, the present study aimed to identify and document the ethnobotany of edible plants in Zebarkhan rangelands located in Razavi Khorasan province. In this study, the traditional beliefs and knowledge of the people about plants were collected in the form of free interviews, participatory observation and continuous presence in 2017-2018. Snowball and purposive sampling were done in order to select participants. The questions posed with the focus on the local names, vegetative forms, methods of harvesting, the organ used, consumption, and plants attributes. The interviews were then continued until the repetitive responses would confirm the reliability and validity of the interview. Finally, the information were classified, analyzed and the key concepts were extracted based on the goal of research.The findings showed that except for the provision of annual food and medical supplies, most of the identified species consisted of multifunctional medicinal and livestock usage and they were also involved with the provision of the livelihood of the residents through collection and sale or forage livestock. The results and findings of this research can be used as a basis for future research on the development of nutrition knowledge and management of rangelands through the improvement and revival with edible and medicinal plants.